New authoritarianism : challenges to democracy in the 21st century - Wiatr, Jerzy J. 1931- HerausgeberIn (Barbara Budrich Publishers, 2019)
The authors deal with comparative aspects of contemporary authoritarianism. Authoritarian tendencies have appeared in several “old democracies” but their main successes take place in several states which departed from dictatorial regimes recently. The book contains case-studies of contemporary Hungarian, Kenyan, Polish, Russian and Turkish regimes.